Comparative Study of Cognitive Skills, Interpersonal Skills and Responsibility of Thai Qualifications Framework for Higher Education and Learning Satisfaction by Using Group Activity in Business Finance Subject - Hirannapat, Mintmanta (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The objective of this research was 1) to compare cognitive skills, interpersonal skills and responsibility of Thai Qualifications Framework for Higher Education and 2) to study learning satisfaction level of using group activity. The sample were 153 students in Faculty of Management Science in Nakhon Pathom Rajabhat University. They studied Business Finance subject in the second semester of the academic year 2014. The Questionnaire was used as the tool for data collection. The data was analyzed in term of frequency, percentage, means, standard deviation and Paired Sample T-test. The results from this research indicated that: 1. After using group activity, cognitive skills level of Thai QualificationsFramework for Higher Education was significantly higher than before, at level of .00. Moreover, Interpersonal Skills and Responsibility of Thai Qualifications Framework for Higher Education after using group activity was significantly higher than before, at level of .00 2. Learning satisfaction level of using group activity in Business Finance Subject was at the high level (M = 4.22, S.D = 0.60). Article history : Accepted 8 June 2015 SIMILARITY INDEX = 3.62